Efeitos da aplicação de composto orgânico de lixo urbano e de fertilizante mineral em povoamentos de eucalyptus grandis W. Hill ex Maiden - Andrade, Guilherme de Castro (2013)
ABSTRACT Large quantities of organic wastes are produced mainly in big cities, annually. There is urgent demand for safe and possibly economic practices for its use. Forest plantations have been studied as a potential ecosystem able to absorb organic residues as fertilizers or soil conditioners. This study evaluated the effects of the application of 15 tons/ha of composted organic waste of the city of São Paulo, and mineral fertilizers in a Eucalyptus grandis plantation on a very poor sandy soil, (NEOSSOLO QUARTZARÊNICO Órtico típico, according to the Brazilian soil classification). It was measured wood production, nutrient contents (N, P, K, Ca and Mg) in the components of the litter and of the trees and the physical and chemical changes in the soil properties, 86 months after the establishment of the plantation. It was studied the decomposition of the litter and the nutrient flow through rainfall, throughfall and stemflow, between 30 and 60 months of age of the trees. Nutrient budgets were obtained taking into account tree biomass data and nutrient contents of the litter and above ground parts of the trees at seven years of age. It was observed that the municipal composted organic wastes resulted in a increase of 45.6% in wood volume and 36.5% in biomass of the trunk under bark, as compared to the control. It also increased the velocity of the litter decomposition on average of 28% and 16% for leaves and twigs respectively, increased the base saturation and the pH level and the availability of water in the soil (from 13% to 25% more available water in the first layer of the soil, 0-10 cm). The balance of nutrients, in the test plots, showed that those plots that received municipal composted organic wastes presented the largest contents of N, P, K and Ca, 86 months after the establishment. As well, after harvesting, remained the largest nutrient pools in the same plots, contributing significantly to keep the forest productivity. The rain also contributed to the replacement of nutrients, 36% of N, 28% of P, 73% of K, 65% of Ca and 42% of Mg of total exported during wood harvesting. This study emphasized again the importance to keep the bark on site to the economy of nutrients. The bark accounted for about 32% of the amount of nutrients present in the above ground biomass of the trees. The large quantity of nutrients in the liter highlights the importance to conserve the organic matter to contribute to the sustainability of the production system